An exploration of caregiver burden for children with nodding syndrome (lucluc) in Northern Uganda. Issue 1 (December 2016) - Nakigudde, Janet; Mutamba, Byamah; Bazeyo, William; Musisi, Seggane; James, Okello
Abstract Background Caregivers of patients with chronic illnesses are often uncompensated for work that is physically demanding, time consuming and emotionally and economically draining. This is particularly true for caregivers of children with nodding syndrome, an emergent neurological disorder of unknown etiology in resource poor settings in Africa. We aimed to explore perceptions of caregivers regarding challenges that a typical caregiver faces when caring for a child with nodding syndrome. Methods We used a qualitative exploratory study design with focus group discussions and in-depth interviews to collect data. We analyzed data using the qualitative analysis software package of NVivo and thematic query building. Results Emergent themes centered on burden of care with emotional agony as the most prominent. Subthemes reflecting the burden of care giving included child and caregiver safety concerns, burnout, social isolation and rejection, and homicidal ideation. Caregivers also complained of physical and financial constraints associated with the care of children with nodding syndrome. Conclusions The findings point to a high burden of care for caregivers of children with nodding syndrome and suggests the need to incorporate community-based psychosocial and mental health care services for the caregivers of affected children into the national health system response.